Vaginal microbiota dysmicrobism and role of biofilm-forming bacteria. - Campisciano, Giuseppina; Zanotta, Nunzia; Petix, Vincenzo; Corich, Lucia; De Seta, Francesco; Comar, Manola (Front Biosci (Elite Ed), 2018)
Bacterial vaginosis involves the presence of a polymicrobial biofilm on the vaginal epithelium, guaranteeing immune escape and spread of antibiotic resistance. To spot known biofilm-forming bacteria, we profiled the vaginal microbiome of sixty-four symptomatic women suffering from a different grade of vaginal disorders and sixty asymptomatic healthy women. Specific microbial profiles distinguished symptomatic from asymptomatic women and characterized the grade of dysmicrobism within the symptomatic group. Lactobacillus crispatus and iners predominated on the healthy vaginal mucosa, while Lactobacillus gasseri predominated in the intermediate dysmicrobism. Furthermore, the intermediate grade of dysmicrobism was characterized by other lactic acid-producers species than Lactobacilli, able to rescue the microbial imbalance, and Ureaplasma parvum-serovar 3. The vaginosis group exhibited the overgrowth of Prevotella bivia, which is known to enhance the biofilm formation by Gardnerella vaginalis, and the presence of Streptococcus anginosus, which is emerging as a new cooperating player of the vaginal biofilm. Identifying specific microorganisms promoting or preventing the biofilm formation could increase the accuracy for a better definition of the vaginal dysmicrobism concept and therapeutic intervention.
Keywords: Adult; Biofilms; Female; Humans; Microbiota; Vagina; Vaginosis, Bacterial

Vanishing Bile Ducts in the Long Term after Pediatric Hematopoietic Stem Cell Transplantation. - Maximova, Natalia; Sonzogni, Aurelio; Matarazzo, Lorenza; Ghirardi, Arianna; D'Antiga, Lorenzo (Biol Blood Marrow Transplant, 2018)
There are no structured studies on liver histology after hematopoietic stem cell transplantation (HSCT). We aimed to prospectively describe the clinicopathologic features of liver disease in the long term after HSCT in an observational, longitudinal study of liver histology in a consecutive cohort of children undergoing allogeneic HSCT. First liver biopsy was performed in presence of abnormal liver function tests and repeated per protocol thereafter. A previously reported semiquantitative score evaluating inflammation, cholestasis, and ductopenia (bile ducts-to-portal tracts ratio ≤ .5) was adopted. Graft-versus-host disease (GVHD) was diagnosed according to standard criteria. We evaluated 131 biopsies taken in 50 HSCTs performed in 47 children (mean age, 9.7 ± 5.2 years). Pre-HSCT chemotherapy was administered in 36 of 50 (72%). GVHD was diagnosed in 17 of 50 (34%). Over time the overall score decreased from a mean of 6 ± 2.7 to 3.25 ± .96 (P < .01), inflammation from 1.22 ± 1.19 to 1 ± 0 (not significant), and cholestasis from 3.9 ± 2.08 to 1.5 ± .58 (P < .01). Ductopenia, found in 113 of 131 biopsies (93%), worsened from .63 ± .35 to .16 ± .14 (P < .01). On multivariate analysis severe ductopenia (ratio ≤ .2) was associated with previous chemotherapy (P = .04), in particular with thiotepa, but not with history of GVHD. Vanishing bile duct syndrome after HSCT may be due to drug-induced liver disease. Longer follow-up will reveal whether these patients are prone to late liver-related morbidity and mortality.

Validation of the Italian translation of the affective neuroscience personality scales. - Pascazio, Lorenzo; Bembich, Stefano; Nardone, Ilaria B; Vecchiet, Cristina; Guarino, Giuseppina; Clarici, Andrea (Psychol Rep, 2015)
The theoretical perspective on affective neuroscience advanced by Panksepp, identified six basic innate affective systems: the SEEK, FEAR, ANGER, SADNESS, PLAY, and CARE systems. (3) It has been proposed that the fundamental elements of human personality and its variants may be based on the different expressions of these basic emotional systems and their combinations. A self-report inventory, the Affective Neuroscience Personality Scales (ANPS), has been devised with the aim of studying and evaluating personality from this perspective. This study reports data on the initial validation of ANPS Italian translation on a sample of 418 adult participants. Descriptive statistics for each scale were calculated, assessing also their internal consistency, as a measure of reliability and factorial validity. Acceptable internal consistency was found in all but one scale (SADNESS), and a second-order factor analysis identified a more general affective feature of personality hinging on relational characteristics, independent of the dimensions of general positive and negative affect.
Keywords: Adolescent; Adult; Affect; Aged; Aged, 80 and over; Female; Humans; Italy; Male; Middle Aged; Neurosciences; Personality; Personality Inventory; Psychometrics; Young Adult

Vitamin D receptor polymorphisms and expression profile in rheumatoid arthritis brazilian patients. - Cavalcanti, Catarina Addobbati Jordão; De Azevêdo Silva, Jaqueline; de Barros Pita, Will; Veit, Tiago Degani; Monticielo, Odirlei Andre; Xavier, Ricardo Machado; Brenol, João Carlos Tavares; Brenol, Cleiton Viegas; Fragoso, Thiago Sotero; Barbosa, Alexandre Domingues; Duarte, Ângela Luiza Branco Pinto; Oliveira, Renê Donizeti Ribeiro; et al. (Mol Biol Rep, 2015)
Rheumatoid arthritis (RA) is an autoimmune disease characterized by chronic inflammation and important joint commitment, being the most common systemic autoimmune disease worldwide. RA displays important genetic background with a variety of genes contributing to the immune balance breakdown. Recent studies have demonstrated that vitamin D, through its receptor (VDR), is able to regulate the immune balance and suppress the autoimmunity process, being a potential target in autoimmune diseases. In the present genetic association study, we assessed 5 Tag single nucleotide polymorphisms (SNPs) (rs11168268, rs2248098, rs1540339, rs4760648 and rs3890733), which cover most of the VDR gene, in three different Brazilian populations (from Northeast, Southeast and South Brazil). We also evaluated the VDR expression profile in whole blood and monocytes from RA patients. For genotyping study, 428 RA patients and 616 healthy controls were genotyped with fluorogenic allele specific probes on an ABI7500 platform. For gene expression study, VDR mRNA levels of 15 RA patients and 26 healthy individuals were assessed by RT-PCR. Our results showed that SNPs rs4760648 and rs3890733 are associated to RA susceptibility (p value = 0.0026, OR 1.31 and p value = 0.0091, OR 1.28 with statistical power = 0.999 and 0.993, respectively). Regarding RA clinical features, the studied SNPs did not show significant associations. The gene expression assays showed that VDR mRNA levels were down regulated in both whole blood (-3.3 fold) and monocytes (-3.2 fold) of RA patients when compared to healthy controls. Our results, the first reported for distinct Brazilian populations, support a role of the VDR gene in the susceptibility to RA.

Validation of point-of-care testing for coeliac disease in children in a tertiary hospital in north India. - Singh, Prashant; Wadhwa, Nitya; Chaturvedi, Mona K; Bhatia, Vidyut; Saini, Savita; Tandon, Nikhil; Makharia, Govind K; Maki, Markku; Not, Tarcisio; Phillips, Alan; Bhatnagar, Shinjini (Arch Dis Child, 2014)
OBJECTIVE: Some of the conventional serological tests for coeliac disease (CD) are expensive, time-consuming and not readily available in developing countries, leading to a delay in diagnosis. Recently, point-of-care tests (POCT) have been manufactured and tested in Europe but have not been validated in our setting. We therefore aimed to study the diagnostic accuracy of the POCT 'Biocard' test in diagnosing CD in Indian children. DESIGN: Cross-sectional study. SETTING: Tertiary care centre in north India. PATIENTS: Children, aged 2-18 years, with chronic diarrhoea, short stature or refractory anaemia underwent serological testing for CD with antiendomysial antibodies (AEA), antitissue transglutaminase (tTG) antibodies and Biocard test followed by duodenal biopsy irrespective of serological results. CD was diagnosed with positive AEA and duodenal biopsy showing >grade 2 changes using modified Marsh criteria. Those who were both AEA negative and had normal histology were considered CD negative. RESULTS: Of 319 children who underwent the serological testing, 170 agreed for biopsy. Of these, 110 were diagnosed with CD and 30 were found to be CD negative. Remaining 30 had discordant AEA and histology results and were not included in analysis. Biocard test agreed with 92/110 positive and 27/30 negative diagnoses based on reference tests (83.6% sensitivity and 90% specificity). tTG was found to be 93.8% sensitive and 96.4% specific. CONCLUSIONS: We successfully validated the POCT for CD in our setting. It could be used to increase case detection rates in developing countries with a large undiagnosed CD burden.
Keywords: Adolescent; Celiac Disease; Child; Child, Preschool; Cross-Sectional Studies; Female; Humans; India; Male; Point-of-Care Systems; Sensitivity and Specificity; Serologic Tests; Tertiary Care Centers

Videogame playing as distraction technique in course of venipuncture. - Minute, M; Badina, L; Cont, G; Montico, M; Ronfani, L; Barbi, E; Ventura, A (Pediatr Med Chir, 2012)
BACKGROUND: Needle-related procedures (venipuncture, intravenous cannulation) are the most common source of pain and distress for children. Reducing needle related pain and anxiety could be important in order to prevent further distress, especially for children needing multiple hospital admissions. The aim of the present open randomized controlled trial was to investigate the efficacy of adding an active distraction strategy (videogame) to EMLA premedication in needle-related pain in children. METHODS: One-hundred and nine children (4 -10 years of age) were prospectively recruited to enter in the study. Ninety-seven were randomized in two groups: CC group (conventional care: EMLA only) as control group and AD group (active distraction: EMLA plus videogame) as intervention group. Outcome measures were: self-reported pain by mean of FPS-R scale (main study outcome), observer-reported pain by FLACC scale, number of attempts for successful procedure. RESULTS: In both groups FPS-R median rate was 0 (interquartile range: 0-2), with significant pain (FPS-R > 4) reported by 9% of subjects. FLACC median rate was 1 in both groups (interquartile range 0-3 in CC group; 0-2 in AD group). The percentage of children with major pain (FLACC > 4) was 18% in CC group and 9% in AD group (p = 0.2). The median of necessary attempts to succeed in the procedures was 1 (interquartile range 1-2) in both groups.. CONCLUSION: Active distraction doesn't improve EMLA analgesia for iv cannulation and venipuncture. Even though, it resulted in an easily applicable strategy appreciated by children. This technique could be usefully investigated in other painful procedures.
Keywords: Anesthetics, Local; Child; Child, Preschool; Female; Humans; Lidocaine; Male; Pain; Phlebotomy; Prilocaine; Prospective Studies; Video Games

Vertebral defects in patients with Peters plus syndrome and mutations in B3GALTL. - Faletra, Flavio; Athanasakis, Emmanouil; Minen, Federico; Fornasier, Federico; Marchetti, Federico; Gasparini, Paolo (Ophthalmic Genet, 2011)
Keywords: Abnormalities, Multiple; Alternative Splicing; Child, Preschool; Cleft Lip; Consanguinity; Cornea; Female; Galactosyltransferases; Glucosyltransferases; Growth Disorders; Humans; Limb Deformities, Congenital; Point Mutation; Spine